REFLEKSI KRITIS TEOLOGI FEMINIS TERHADAP INSTRUMENTALISASI MAKNA BELIS PADA MASYARAKAT SIKKA KROWE - Monteiro, Yohanes Hans; Manuk, Martinus Burong; Mite, Petrus Kanisius Mbulu; Jewadut, Jean Loustar (Bahasa Indonesia, 2025)
This article explains the critical reflection of feminist theology in the face of the phenomenon of instrumentalization of the meaning of belis in the Sikka Krowe society. Belis, which has a noble meaning, is instrumentalized by certain parties as an event to gain economic benefits. This article is written using qualitative research. Data was mainly collected through individual interview. To deepen the analysis, a reference study related to feminist theology was also made which is linked to the problem of instrumentalization of the meaning of belis in Sikka Krowe society. The results of this study show that women are more often positioned as objects to gain economic profits from the amount of belis given by men. The larger the number of belis given, the more the male side has full power over the position of women. In the face of this phenomenon, feminist theology must convey its critical voice by taking three rare steps, namely socioanalytic steps, hermeneutical steps, and praxis steps.